Unlocking Vocabulary Potential: How Quizlet Enhances Learning for Seventh-Grade Students - Putri, Adeliany; Pratiwi, Dwiyani; Afifah, Tasya (International Journal of Contemporary Studies in Education, 2024)
Students struggle to understand their teacher due to difficulties in memorizing vocabulary and comprehending word definitions. This research focuses on two key questions: (1) How do seventh-grade students at MtsN 1 Bengkalis respond to using Quizlet as a learning tool? and (2) How does Quizlet help improve their vocabulary knowledge? The study aims to enhance vocabulary learning for seventh graders and assess their reactions to using Quizlet at MtsN 1 Bengkalis, Riau, during the 2022/2023 academic year. The research method used is classroom action research. The findings show a significant improvement in students' vocabulary knowledge across three tests. The average score in test 1 was 60.6, in test 2 it rose to 68.75, and in test 3 it further increased to 80.0. In conclusion, Quizlet has proven to be an effective tool for improving vocabulary learning in students